RECONCILIATION OF THE THEORY OF NĀSIKH - MANSŪKH IN THE QUR'AN VERSION OF SAYYID QUTHB: An Analysis of the Tafsir of Fi-Zhilalil Qur'an - Nursyamsu, Nursyamsu; Taufiq, Muhammad; Maliki, Maliki; Najmuddin, Hasan Asy’ari (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
The study of nāsikh - mansūkh has recently become an interesting study in the theory of the development of the ulumul Qur'an. This is of course seen in several aspects of the study of nāsikh - mansūkh carried out by several previous studies. However, what is more interesting is that research regarding nāsikh - mansūkh is still being carried out by several tafsir scholars, namely Sayyid Quthb in his book Fi Zhilalil-Qur’an. In his tafsir book, there are several terms that researchers see as the existence of nāsikh - mansūkh in tafsir. Of course this is an academic problem in this research. More specifically, this article will answer several main issues for further study. First, what is Sayyid Quthb's view of the nāsikh - mansūkh theory in the commentary book Fi Zhilalil-Qur’an. Second, what are the themes that nāsikh - mansūkh uses as a form of reconciliation with Sayyid Quthb in his tafsir book. This type of research is a descriptive-analytical library study by analyzing various relevant references to answer the main problem, including books, journals, articles and several other references. This article concludes that Sayyid Quthb succeeded in showing the verses of the Qur’an which are considered naskh in the book Fi Zhilalil-Qur’an. Sayyid Quthb's view divides the naskh into two, namely nāsikh tāsyri’i and nāsikh takwiniy. Naskh tasyri’i is an erasure that does not occur in the Qur'an meaning, there is no naskh between other verses of the Qur'an. because the tasyri’i naskh process was final with the end of the Prophet's message. Meanwhile, naskh takwiniy is the occurrence of a miraculous event which is a manifestation of God's intervention in the wheel of human life. The form of relevance of the nāsikh - Mansūkh theory carried out by Sayyid Quthb is that all the messages put forward by the Qur'an are systematic-implementative. This means that the entire message of the Qur'an is an inseparable unity and is integrally ready to be applied in the real life of humanity throughout the ages.